Investigation of a fibre-optic Fizeau interferometer configuration and coherent fibre-optic imaging bundles for optical coherence tomography - Sarantavgas, Georgios (Cranfield University, 2008)
Currently several medical imaging techniques are in operation in clinical environments that help the doctors to diagnose diseases before proceeding to treatment. This research investigated and implemented configurations for a medical imaging technique called Optical Coherence Tomography (OCT). The Michelson interferometer has been the principal configuration for OCT systems. For endoscopic OCT applications though such a configuration is susceptible to polarisation induced signal fading due to environmental changes within the sample arm, like fibre bending and temperature fluctuations. The development and testing of a Fizeau interferometer based OCT system demonstrate the elimination of this polarisation induced signal fading as the sample and reference arm of the interferometer experience the same environmental changes. The Fizeau interferometer is formed between the end of the fibre and the sample itself. A secondary processing interferometer is used in this configuration, to compensate the path difference inherent to the Fizeau configuration. Longitudinal resolution is about 19 m in air, and lateral resolution about 23 m. A signal-to-noise ratio of about 80 dB was achieved with this system and several sets of image data were collected from laboratory and biological samples. An OCT system based on a Fizeau interferometer incorporating a coherent fibre imaging bundle was also investigated. Fibres in the bundle are accessed sequentially by a beam focused onto the input face of the bundle, allowing 2D information to be acquired using point detection. Incorporating a fibre optic imaging bundle in Fizeau based interferometer OCT allows mechanical scanning parts to be removed from the sample arm, resulting in a passive probe. Such a configuration can form a compact, robust and “downlead insensitive” OCT system and is a strong candidate for in vivo applications. The performance of leached and wound coherent fibre optic bundles was accessed and an analysis is presented. The longitudinal resolution of the system developed was about 10 m in air, and lateral resolution about 9 m. This thesis demonstrates several sets of image data that were collected from various samples using a Fizeau interferometer based OCT incorporating coherent imaging bundles. 2D image data captured by such a configuration are presented and reported for the first time in this thesis.